Cost and robotic surgery in gynecology. Issue 1 (11th October 2013) - Knight, Jason; Escobar, Pedro F.
Abstract Since the introduction of robotic technology, there have been significant changes to the field of gynecology. The number of minimally invasive procedures has drastically increased, with robotic procedures rising remarkably. To date several authors have published cost analyses demonstrating that robotic hysterectomy for benign and oncologic indications is more costly compared to the laparoscopic approach. Despite being more expensive than laparoscopy, other studies have found robotics to be less expensive and more effective than laparotomy. In this review, controversies surrounding cost‐effectiveness studies are explored.